Model Pembelajaran Berbasis STEAM Projek untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa - Sari, Dyah Puspita; Hasanah, Daimul; Barriyah, Insanul Qisti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
This research aims to analyze influence of the STEAM Project learning model (Science, Technology, Engineering, Arts, and Mathematics) on students' critical and creative thinking abilities. The research was conducted on 15 class studentsVI at one of the elementary schools in Kulon Progo consisting of 8 male and 7 female students. The method used in this research is descriptive qualitative with interview and observation techniques. Results Study Demonstrated better critical thinking and creativity skills and increased at the third and fourth meetings. At the third meeting, students began to show their ability to solve problems, namely by making a mechanical power generator. The ability to think creatively was seen at the third and fourth meetings, namely when their dream house was realized which looked aesthetic and beautiful. The final product of this activity is the result of project activities in the form of a miniature house with installation and electricity generator. The STEAM Project-based learning model has encouraged students to be able to plan problem solutions, be flexible in providing solutions, and create product designs that have aesthetic value.